2020
DOI: 10.1371/journal.pone.0239205
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for grain yield and other traits in tropical maize under Striga infestation

Abstract: Striga is an important biotic factor limiting maize production in sub-Saharan Africa and can cause yield losses as high as 100%. Marker-assisted selection (MAS) approaches hold a great potential for improving Striga resistance but requires identification and use of markers associated with Striga resistance for adequate genetic gains from selection. However, there is no report on the discovery of quantitative trait loci (QTL) for resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 67 publications
2
26
1
Order By: Relevance
“…High broad-sense heritability estimates for GY, AUSNPC, SDR and number of emerged Striga plants 12 WAP suggest that the actual narrow-sense heritability could be higher and that reasonable genetic gain for these traits could be expected. The high broad-sense heritability estimates for GY (0.70) and number of emerged Striga plants 12 WAP (0.68) observed in this study corroborate previous reports under artificial Striga infestation (Menkir et al 2012 ; Makumbi et al 2015 ; Adewale et al 2020 ) and higher than the heritability observed in biparental populations (Badu-Apraku et al 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High broad-sense heritability estimates for GY, AUSNPC, SDR and number of emerged Striga plants 12 WAP suggest that the actual narrow-sense heritability could be higher and that reasonable genetic gain for these traits could be expected. The high broad-sense heritability estimates for GY (0.70) and number of emerged Striga plants 12 WAP (0.68) observed in this study corroborate previous reports under artificial Striga infestation (Menkir et al 2012 ; Makumbi et al 2015 ; Adewale et al 2020 ) and higher than the heritability observed in biparental populations (Badu-Apraku et al 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one SNP S3_158421414 detected consistently for number of emerged Striga plants at 10 and 12 WAP and AUSNPC was overlapped with the QTL reported by Badu-Apraku et al ( 2020a ) in biparental population. In this study, no overlapping of SNPs was detected between number of Striga -emerged plants and SDR, however five SNPs on chromosome 3 ( S3_143803575 , S3_143804650, S3_145603175, S3_145603187 and S3_158421414 ) detected for number of Striga -emerged plants were overlapped with four QTL detected for SDR in an earlier study (Badu-Apraku et al 2020b ) which suggests this region might be carrying an important gene/s for resistance to Striga .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of resistance has proven to be strenuous due to its low heritability [ 16 , 17 ]. Marker identification will formulate tools that are faster, cheaper, and easier to utilise in effectively tackling the problem of breeding for Striga resistance [ 13 , 18 , 19 ]. There is a research gap on the use of SNP markers to improve maize genotypes to resist Striga infestation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is need to identify SNP markers in maize that are associated with resistance to Striga using genome-wide association study (GWAS) because SNP markers are abundantly available in the maize genome, codominant, evenly distributed throughout the genome, and highly reproducible and polymorphic. However, to date, only reports exist for Striga hermonthica found in east Africa and absent for Striga asiatica found in southern Africa [ 13 , 18 , 21 , 22 ]. Identification of SNP markers will solidify convectional breeding methods and bring rejuvenation to maize production in resource poor African farmers by reducing yield losses due to Striga infestation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%